AI-Augmented Resilience Through Smart TV-Mediated Learning: A Qualitative Case Study of Academic Resilience, Psychological Well-Being, and Growth Mindset Among Senior High School Students - Norhidayah Norhidayah; Arina Restian; Husamah Husamah (Universitas Pendidikan Mandalika, 2026)
This study explores how the integration of artificial intelligence (AI) through Smart TV/Interactive Flat Panel (IFP) technology was perceived by students and teachers as a classroom-based psycho-pedagogical support mechanism for Grade X students at SMAN 1 Mentaya Hilir Selatan, East Kotawaringin, Indonesia. While AI in education is commonly examined as a cognitive tool for personalized instruction, less attention has been paid to its affective and communal roles in strengthening students' coping experiences, emotional safety, and willingness to revise mistakes. The study was conducted during one semester from October 2025 to February 2026 in Grade X learning activities involving English, history, coding, and informatics lessons. The AI tools used included ChatGPT, Gemini, Copilot, Perplexity, or school-approved AI assistant, which were accessed through teacher-led and student-assisted classroom routines and displayed on Smart TV/IFP screens. This study employed a descriptive qualitative case-study design involving 21 informants: 15 Grade X students and six supporting school informants consisting of the vice principal for curriculum affairs, counseling teacher, and subject teachers. Data were collected through in-depth interviews, classroom observation, digital documentation, and learning artifacts, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal three central mechanisms. First, AI served as a non-judgmental dialogic partner that helped students break down difficult tasks, regulate frustration, and recover from academic setbacks. Second, the large-screen display created a Digital Mirroring Effect, in which the visible process of AI-supported trial, error, and revision normalized mistakes and encouraged a growth mindset. Third, teacher and counselor facilitation transformed AI-Smart TV integration into a safer classroom ecology that reduced academic anxiety and improved students' perceived psychological well-being. However, a negative case also indicated the risk of digital dependency when AI was used merely to copy answers. The study proposes AI-Augmented Resilience and Digital Mirroring Effect as interpretive, case-based psycho-pedagogical mechanisms,emphasizing that AI is most educationally productive when mediated by shared visualization, ethical guidance, and authentic assessment.